Echocardiographic findings in patients post covid-19 centro cardiovascular regional (Boletin Médico de Postgrado, 2025)
The pandemic produced by coronavirus disease 2019 (COVID-19) has caused considerable morbidity and mortality worldwide due to the involvement of multiple systems, within them, the cardiovascular system. The aim of the present study was to analyze echocardiographic findings in 640 post-COVID-19 patients referred to the Echocardiography Service of the Regional Cardiovascular Center (RCC) from October 2020 to March 2023. A descriptive, cross-sectional, single-center design was used. The mean age of the patients was 50.5 ± 15.1 years, with female sex predominating (68.9%). The results showed that right and left ventricular dimensions and LV end-diastolic and end-systolic volumes and left atrial volume were normal. LV ejection fraction was found to be preserved in 96% of patients with a mean of 62.9 ± 6.7%, as was RV function with a mean TAPSE of 23 mm ± 18.1; tricuspid S velocity was 12.3 cm/s and tricuspid E/A ratio of 1.3. The most frequent alteration was pericardial refractoriness (39.7%), with this finding predominating in the female sex (74%) and between the first and third month after the echocardiogram was performed (40.94%). Pericardial thickening was evident in 14.4% of patients and pericardial effusion in 6.3%. There was no evidence of pulmonary hypertension. Cardiovascular alterations after COVID-19 infection are rare and generally mild, even when evaluated during the first weeks after recovery from the disease.